Reforming the Polish Tax System to Improve its Efficiency - de Serres, Alain (OECD Publishing, 2008)
The Polish tax system is characterised by high social security contributions for both employers and employees. As a result, Poland has one of the highest tax wedges in the OECD, despite relatively low personal income tax rates. This, combined with a relatively high minimum wage and generous early-retirement and disability benefit programmes, contributes to low employment rates, in particular among low-skilled workers. The system also relies heavily on consumption taxes, whereas relatively little revenue is collected from such bases as environment externalities, inheritances and, in particular, property. One of the key implications of the tax structure is that the system as a whole is one of the least redistributive among OECD countries. This paper reviews the main features of the tax system and explores options to improve its efficiency, including possibilities to broaden existing tax bases as well as to shift the tax burden from labour towards less mobile and distorting sources such as property
Keywords: Economics; Poland